Coastal proximity and individual living standards: Econometric evidence from georeferenced household surveys in sub-Saharan Africa - Wild, Frederik; Stadelmann, David (Multiplicity in Decision-Making of Africa's Interacting Markets: The Functioning of Community Law, the Role of Market Participants and the Power of Regional Judges (MuDAIMa), 2021)
We investigate geo-referenced household-level data consisting of up to 206,896 individuals living in 21,826 localities across 28 sub-Saharan African countries over 20 years. We analyse the relevance of coastal proximity as a predictor of individual economic living standards. Our results highlight the role of human capital as well as infrastructural endowments in reconciling the large intra-national disparities in individual economic welfare.
Keywords: Geography; Sub-Saharan Africa; Mediation (Statistics); Coastal Proximity; Mediation Analysis; Coastal Countries; Econometric Evidence; Household Survey